Phylogenomic relationships of rice oxalate oxidases to the cupin superfamily and their association with disease resistance QTL - Carrillo, Maria Gay C.; Goodwin, Paul H.; Leach, Jan E.; Leung, Hei; Vera Cruz, Casiana M. (Springer, 2009)
Rice oxalate oxidase genes (OXO) may play a role in resistance to Magnaporthe oryzae. Genome analyses showed four tandemly duplicated OXO genes, OsOXO1–OsOXO4, which mapped to a blast resistance QTL in chromosome 3. These genes have >90% nucleotide and amino acid identity, but they have unique gene structures, conserved motifs, and phylogeny compared to the 70 other members of the cupin superfamily in the Nipponbare genome, which were divided into several classes. In resistant and susceptible Vandana/Moroberekan advanced backcross lines, only OsOXO4 was expressed during rice–M. oryzae interactions, and its expression increased earlier in resistant than susceptible lines. The earlier expression of OsOXO4 in resistant lines correlated with a 26-bp promoter insertion containing an additional copy of the bacterial responsive nodulation cis-element. Our results showed that OsOXO1–4 are in a separate class of rice cupin genes and supports a role for the promoter variant of OsOXO4 in resistance to M. oryzae.